The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1177/0022343314527983
|View full text |Cite
|
Sign up to set email alerts
|

Foreign policies or culture

Abstract: This analysis uses survey data representing three of the world's most populous Muslim majority countries to challenge conventional wisdom on what shapes Muslim public opinion on political violence against the United States. It improves previous analysis by clearly distinguishing support for violence against civilians from support for violence against military targets and by featuring independent variables that clearly separate views on US foreign policies from views on US culture. Logistic regression shows tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…As such, the sense that another group poses a material resource threat is likely to make one feel that one's group esteem has been lowered and one's group has been demeaned, posing a threat to the symbolic resource of group pride. As Muslim-dominated Arab nations on average are substantially less wealthy than the U.S. (Fund for Peace 2011), and there is a recent history of Christian nations becoming predominant over Muslims or occupying Muslim lands, many Muslim Arabs feel they are being exploited and controlled by American desires for domination, which they find demeaning and humiliating (e.g., Fattah and Fierke 2009;Kohut 2005;Little 2002; see also Berger 2014). Given the thrust of Hezbollah's resistance agenda (e.g., resistance to American domination), we expect perceptions that Americans threaten to dominate Arabs' material (e.g., economic) and symbolic resources (e.g., group esteem) to be more strongly associated with support for Hezbollah than Al Qaeda among our participants (see also Sidanius et al 2015).…”
Section: Comparison Of Hezbollah and Al Qaedamentioning
confidence: 99%
See 1 more Smart Citation
“…As such, the sense that another group poses a material resource threat is likely to make one feel that one's group esteem has been lowered and one's group has been demeaned, posing a threat to the symbolic resource of group pride. As Muslim-dominated Arab nations on average are substantially less wealthy than the U.S. (Fund for Peace 2011), and there is a recent history of Christian nations becoming predominant over Muslims or occupying Muslim lands, many Muslim Arabs feel they are being exploited and controlled by American desires for domination, which they find demeaning and humiliating (e.g., Fattah and Fierke 2009;Kohut 2005;Little 2002; see also Berger 2014). Given the thrust of Hezbollah's resistance agenda (e.g., resistance to American domination), we expect perceptions that Americans threaten to dominate Arabs' material (e.g., economic) and symbolic resources (e.g., group esteem) to be more strongly associated with support for Hezbollah than Al Qaeda among our participants (see also Sidanius et al 2015).…”
Section: Comparison Of Hezbollah and Al Qaedamentioning
confidence: 99%
“…These kinds of value threats have been recognized by symbolic racism theory (Sears 1988), value-conflict theory (Henry and Reyna 2007), the sociofunctional approach to prejudice (Cottrell and Neuberg 2005;Neuberg and Cottrell 2002), and image theory's dimension of cultural inferiority (Alexander, Brewer, and Herrmann 1999). Studies have shown that many Muslims living in primarily Muslim nations view American culture as vulgar, disrespectful, and obscene regarding sexuality, and are offended by U.S. gender relations and freedom of expression (e.g., Garfinkle 2004;Glazov 2004; see also Berger 2014). When people sense that their sacred values, revered objects, or other sacrosanct intangibles have been violated by those not viewed as pure, they become repulsed and reject or remove the sources of these value threats (Greenberg et al 1995;Tetlock et al 2002).…”
Section: Comparison Of Hezbollah and Al Qaedamentioning
confidence: 99%
“…In spite of the evidence that has been amassed for each of these theoretical perspectives, they have only very rarely been compared to one another empirically (but see Berger, 2014; Mostafa & El-Hamdi, 2007; Sidanius et al, 2004). Moreover, little is known about potential moderators of each of these three predictors of support for asymmetric violence.…”
mentioning
confidence: 99%
“…According to Ross (2010), anti-US sentiments worldwide are significantly causative to the US recession. According to Berger (2014), a study conducted by Pew Foundation in Muslim majority countries indicated that the majority of the people in those countries were intended to refuse US products and services. Numerous studies across the Muslim world recently show consumers’ hostility and resentment toward US and European products (Abosag and Farah, 2014; Amine, 2008; Kashif et al , 2015; Maher and Mady, 2010).…”
Section: Introductionmentioning
confidence: 99%